The influence of diet on patients suffering from Fibromyalgia Syndrome - Monika Wendland; Justyna Janikowska; Agata Żak-Gontarz; Julia Piotrowska; Adrianna Domańska; Aleksandra Łubińska-Kowalska; Aleksandra Minda; Antonina Teresa Witkowska; Krzysztof Julian Długosz; Barbara Anna Zapalska; Adrianna Witkowska (Quality in Sport)
Fibromyalgia is a chronic centralized pain syndrome characterized by disordered transmission of pain stimuli. The symptoms of fibromyalgia are very diverse and patients often experience musculoskeletal pain,  fatigue, psychiatric disorders (especially depression), sleep disturbances and gastrointestinal disorders. Since there is no cure for fibromyalgia, the proper diagnosis of the illness and consequently treating fibromyalgia effectively are key factors for reducing symptoms and improving a patient's quality of life.  The review article shows different nutritional  approaches on FM patients that have been researched in recent years and are key factor for integrated recovery plan and managing symptoms. Patients may benefit not only from proper treatment, physiotherapy and psychotherapy, but also from concrete nutritional approach which can influence inflammatory processes and central sensitization which are considered nowadays to play a major role in pathogenesis of the illness. There is not enough evidence that specific diet therapy is to be considered for the treatment of FM. However, overall studies revealed that weight control, anti-inflammatory diets, and vitamin D supplementation are beneficial in managing FM symptoms but further research is needed in this matter.